MATERIALS TO THE FAUNA OF ACRIDOIDEA AND TETRIGOIDEA OF DAGESTAN - E. N. Terskov; G. M. Abdurahmanov (Юг России: экология, развитие)
Clarified the species composition of grasshoppers and tetrigid of Dagestan. The list includes 87 species, of which Chorthippus abchasicus indicated for the first time in the region of the study. Given point of copyright fees locust according to the literature.